Food intake of pregnant women: A study among the pregnant women of a tertiary care hospital in Ajmer, Rajasthan, India - Singh, Deepika; Prakash, Bharti (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Introduction: Nutritional diet is an important pillar of good health during pregnancy. A healthy diet is essential for every pregnant woman especially for the development of foetus. Knowledge and importance about healthy diet is essential for them as they are responsible for the growth of their foetus and her own health in order to prevent adverse pregnancy outcomes. Objective: To determine the association between intake of nutritional diet and personal habits among pregnant women.Methods: A descriptive cross sectional study was conducted among the pregnant women of a tertiary care hospital of Ajmer. The study included 975 pregnant women. A structured interview questionnaire composed which contained questions regarding their dietary intake. They were asked about the amount of food they consumed and their use of fast food, alcohol, tobacco and sugary snacks. The data collected was tabulated and analyzed.Results: The study revealed that 72.2% of the interviewed women were aged 25-30 years, 66.5% of them were from rural area. Illiterate women represented 35.6% of the studied group. 87.6% of the pregnant women were housewives. Intake of fewer servings than the recommended amount in all food groups was recorded. Pregnant women frequently reduced intake of foods. Due to nausea and vomiting, many pregnant women refused to take proper nutritional diet. Only 58.6% of pregnant women consumed fruits and green vegetables. Majority (52.3%) of pregnant women show high consumption of fast food and sweets. Most of the rural pregnant women used tobacco products which are harmful for their baby. 43.6% pregnant women consumed carbonated drinks instead of fruit juices. Many women used sour, spicy and chilled food due to pregnancy cravings. Only 31.3% of pregnant women consumed milk and sprouts. Positive attitude toward nutritional diet was significantly higher among urban, educated, working and prim gravidae pregnant women (p=0.0001). Conclusion: The study showed that majority (62%) of pregnant women have poor dietary intake with many lacunae present. The different factors responsible for it were determined. Pregnant women can potentially improve their food habits by modifying their lifestyle and following healthier nutritional practices. A better dietary knowledge is necessary for the pregnant women.